Pengembangan Bahan Ajar IPAS Berbasis Komik untuk Meningkatkan Hasil Belajar Siswa Sekolah Dasar pada Materi "Ayo Mengenal Siklus Makhluk Hidup" - Dano, Alfa Andini; Nahak, Kristina E. Noya; Hano, Alvin Javier (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The limited use of innovative teaching materials and the predominance of text based learning resources have contributed to low student engagement and unsatisfactory learning outcomes in the IPAS topic "Let's Learn About Life Cycles." Preliminary findings indicated that only 10 out of 26 third grade students (38.46%) achieved the minimum learning mastery criterion, while 16 students (61.54%) failed to meet the expected standard. This study aimed to develop comic based IPAS teaching materials and examine their validity, practicality, and effectiveness in improving elementary school students' learning outcomes. The study employed a Research and Development approach using the ADDIE model, consisting of Analysis, Design, Development, Implementation, and Evaluation. The research participants were 26 third grade students of UPTD SDI Sikumana 3, Kupang City. Data were collected through observation, interviews, expert validation sheets, teacher and student response questionnaires, and pretest and posttest instruments. The developed teaching materials obtained validity scores of 95.00% from the material expert, 87.50% from the media expert, and 96.66% from the language expert, indicating a very valid category. The implementation results demonstrated a substantial improvement in students' learning outcomes, with the mean score increasing from 34.50 in the pretest to 78.62 in the posttest. The number of students achieving the high achievement category also increased from one student to twenty three students after the intervention. These findings indicate that comic based IPAS teaching materials are valid, practical, and effective in improving elementary school students' understanding of life cycle concepts while promoting more engaging and meaningful learning experiences.